2007
DOI: 10.1007/s10803-007-0501-2
|View full text |Cite
|
Sign up to set email alerts
|

Friendship in High-functioning Children with Autism Spectrum Disorder: Mixed and Non-mixed Dyads

Abstract: Friendships containing a child with autism and a friend with typical development ("mixed" friendships, n = 26) and those of children with autism and a friend with a disability ("non-mixed," n = 16) were contrasted with friendships of typically developing subjects and their friends (n = 31). Measures included dyadic interaction samples, and interview and questionnaire data from subjects, friends, and parents. Mixed friendship interactions resembled typical friendships. Participants in mixed friendships were mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
89
2
5

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(106 citation statements)
references
References 62 publications
6
89
2
5
Order By: Relevance
“…It is possible, as posited by Bauminger and colleagues, that children with ASD who have reciprocal friendships, also have stronger social skills and higher social-emotional abilities than children with ASD who do not have friends (Bauminger et al 2008). If this is the case, the very children who are successful in navigating dyadic relationships might also be the ones who are more aware of their more global social deficits.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible, as posited by Bauminger and colleagues, that children with ASD who have reciprocal friendships, also have stronger social skills and higher social-emotional abilities than children with ASD who do not have friends (Bauminger et al 2008). If this is the case, the very children who are successful in navigating dyadic relationships might also be the ones who are more aware of their more global social deficits.…”
Section: Discussionmentioning
confidence: 99%
“…When examining pragmatic language deficits in ASD, a stated hallmark is impairment in social responsivity and reciprocity (Stefanatos & Baron, 2011). Poor conversational quality emerged in previous studies, including one-sidedness, low quality of facial expression, and less nonreciprocal gaze (Bauminger et al, 2008;Nadig et al, 2010). Intonation -part of the prosodic behavior fostering speakers' production abilities -was found to be of lower quality in HFASD than in TYP (Paul et al, 2009), thereby substantiating the characteristic profile where pragmatics and prosody are impaired to a greater extent in ASD than in TYP (Stefanatos & Baron, 2011).…”
Section: Group Differences In Pragmatic Abilities: Hfasd Versus Typmentioning
confidence: 99%
“…Individuals self-reporting more characteristics of HFA also reported significantly greater loneliness, fewer friendships, and shorter duration of friendships. Moreover, Bauminger et al (2008) have reported lowered friendship quality in individuals with ASD who are worse at emotion recognition and theory of mind skills. Social anxiety however, was not assessed in this study.…”
Section: Relating and Communicating In A Social Contextmentioning
confidence: 99%